Study on the protective effect of berberine treatment on sepsis based on gut microbiota and metabolomic analysis - Pan, Huibin; Huo, Lixia; Shen, Weiyun; Dai, Zhuquan; Bao, Ying; Ji, Chaohui; Zhang, Jie (Frontiers in Nutrition, 2022)
Sepsis, an infection with multiorgan dysfunction, is a serious burden on human health. Berberine (BBR), a bioactive component, has a protective effect on sepsis and the effect may be related to gut microbiota. However, studies on the role of BBR with gut microbiota in sepsis are lacking. Therefore, this study investigated the ameliorative effects and the underlying mechanisms of BBR on cecal ligature and puncture (CLP) rats. Firstly, the inhibition effects of BBR treatment on the histological damage of lung, kidney, and ileum, the interleukin (IL)-1, IL-6, IL-17A, and monocyte chemokine-1 levels in serum in CLP rats were proved. Also, the BBR inhibited the diamine-oxidase and FITC-dextran 40 levels, suggesting it can improve intestinal barrier function disorders. The CD4+, CD8+, and CD25+ Foxp3+ T lymphocytes in splenocytes were up-regulated by BBR, while the IL-17A+CD4+ cell level was decreased. The abundance of gut microbiota in CLP rats was significantly different from that of the sham and BBR treatment rats. The significantly changed metabolites in the serum mainly included carbohydrates, phenols, benzoic acids, alcohols, vitamins et al. Additionally, this study predicted that the biological mechanism of BBR to ameliorate sepsis involves glycolysis-, nucleotide-, and amino acid-related metabolic pathways. This study proved the strong correlation between the improvement effect of BBR on sepsis and gut microbiota and analyzed by metabolomics that they may improve CLP rats through metabolites, providing a scientific basis for BBR to improve sepsis and a new direction for the study of the biological mechanism.